KEPASTIAN HUKUM AKTA PERJANJIAN JUAL BELI YANG OBJEKNYA DIAGUNKAN DI BANK - FENI WULANDARI (PREMISE LAW JURNAL, 2017)
An agreement should meet the requirement for its validity under Article 1320 of the Civil Code. It does not fulfill object element because it becomes the seller’s mortgage in the Bank, and he transfer the land and building without the acknowledge of the Bank, and violates against the provision of Article 11, paragraph (2), letter g of Law No. 4/1996 on Collateral. This research analyzes legal certainty on purchase agreement certificate which object is mortgaged in the Bank made by a Notary without considering the prevailing regulations.The research used juridical normative and empirical and descriptive analytic.The result of the research showed that Purchase Agreement Certificate which object is mortgaged in the Bank is null and void because it does not meet the objective requirements stipulated in Article 1320, paragraphs (3) and (4) of the Civil Code and violates against Article 11, paragraph (2), letter g of Law No. 4/1996 on Collateral. In a Purchase Agreement Certificate which object is mortgaged in the Bank, the Notary as a public official has to comply with Notarial Code of Ethics. Article 15, paragraph (2), letter E of the Notarial Act No. 2/2014. Keywords: Legal certainty, Purchase Agreement, Collateral